Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
When y=0,
[tex]-2{ x }^{ 2 }-5x+3=0\\ \\ 2{ x }^{ 2 }+5x-3=0\\ \\ \left( 2x-1 \right) \left( x+3 \right) =0[/tex]
[tex]\\ \\ \therefore \quad x=\frac { 1 }{ 2 } \\ \\ \therefore \quad x=-3[/tex]
--------------------
[tex]\int _{ -3 }^{ \frac { 1 }{ 2 } }{ -2{ x }^{ 2 } } -5x+3dx[/tex]
[tex]\\ \\ ={ \left[ -\frac { { 2x }^{ 2+1 } }{ 2+1 } -\frac { 5{ x }^{ 1+1 } }{ 1+1 } +3x \right] }_{ -3 }^{ \frac { 1 }{ 2 } }[/tex]
[tex]\\ \\ ={ \left[ -\frac { 2{ x }^{ 3 } }{ 3 } -\frac { 5{ x }^{ 2 } }{ 2 } +3x \right] }_{ -3 }^{ \frac { 1 }{ 2 } }[/tex]
[tex]\\ \\ \\ =\left\{ -\frac { 2 }{ 3 } { \left( \frac { 1 }{ 2 } \right) }^{ 3 }-\frac { 5 }{ 2 } { \left( \frac { 1 }{ 2 } \right) }^{ 2 }+3\left( \frac { 1 }{ 2 } \right) \right\} -\left\{ -\frac { 2 }{ 3 } { \left( -3 \right) }^{ 3 }-\frac { 5 }{ 2 } { \left( -3 \right) }^{ 2 }+3\left( -3 \right) \right\}[/tex]
[tex]\\ \\ \\ =-\frac { 2 }{ 3 } \cdot \frac { 1 }{ 8 } -\frac { 5 }{ 2 } \cdot \frac { 1 }{ 4 } +\frac { 3 }{ 2 } -\left\{ -\frac { 2 }{ 3 } \left( -27 \right) -\frac { 5 }{ 2 } \cdot 9-9 \right\}[/tex]
[tex]\\ \\ =-\frac { 2 }{ 24 } -\frac { 5 }{ 8 } +\frac { 3 }{ 2 } -\left\{ \frac { 54 }{ 3 } -\frac { 45 }{ 2 } -9 \right\}[/tex]
[tex]\\ \\ =-\frac { 2 }{ 24 } -\frac { 15 }{ 24 } +\frac { 36 }{ 24 } -\frac { 54 }{ 3 } +\frac { 45 }{ 2 } +9[/tex]
[tex]\\ \\ =\frac { 19 }{ 24 } -\frac { 54 }{ 3 } +\frac { 45 }{ 2 } +\frac { 18 }{ 2 } \\ \\ =\frac { 19 }{ 24 } -\frac { 54 }{ 3 } +\frac { 63 }{ 2 }[/tex]
[tex]\\ \\ =\frac { 343 }{ 24 } [/tex]
Answer: 343/24 units squared.
[tex]-2{ x }^{ 2 }-5x+3=0\\ \\ 2{ x }^{ 2 }+5x-3=0\\ \\ \left( 2x-1 \right) \left( x+3 \right) =0[/tex]
[tex]\\ \\ \therefore \quad x=\frac { 1 }{ 2 } \\ \\ \therefore \quad x=-3[/tex]
--------------------
[tex]\int _{ -3 }^{ \frac { 1 }{ 2 } }{ -2{ x }^{ 2 } } -5x+3dx[/tex]
[tex]\\ \\ ={ \left[ -\frac { { 2x }^{ 2+1 } }{ 2+1 } -\frac { 5{ x }^{ 1+1 } }{ 1+1 } +3x \right] }_{ -3 }^{ \frac { 1 }{ 2 } }[/tex]
[tex]\\ \\ ={ \left[ -\frac { 2{ x }^{ 3 } }{ 3 } -\frac { 5{ x }^{ 2 } }{ 2 } +3x \right] }_{ -3 }^{ \frac { 1 }{ 2 } }[/tex]
[tex]\\ \\ \\ =\left\{ -\frac { 2 }{ 3 } { \left( \frac { 1 }{ 2 } \right) }^{ 3 }-\frac { 5 }{ 2 } { \left( \frac { 1 }{ 2 } \right) }^{ 2 }+3\left( \frac { 1 }{ 2 } \right) \right\} -\left\{ -\frac { 2 }{ 3 } { \left( -3 \right) }^{ 3 }-\frac { 5 }{ 2 } { \left( -3 \right) }^{ 2 }+3\left( -3 \right) \right\}[/tex]
[tex]\\ \\ \\ =-\frac { 2 }{ 3 } \cdot \frac { 1 }{ 8 } -\frac { 5 }{ 2 } \cdot \frac { 1 }{ 4 } +\frac { 3 }{ 2 } -\left\{ -\frac { 2 }{ 3 } \left( -27 \right) -\frac { 5 }{ 2 } \cdot 9-9 \right\}[/tex]
[tex]\\ \\ =-\frac { 2 }{ 24 } -\frac { 5 }{ 8 } +\frac { 3 }{ 2 } -\left\{ \frac { 54 }{ 3 } -\frac { 45 }{ 2 } -9 \right\}[/tex]
[tex]\\ \\ =-\frac { 2 }{ 24 } -\frac { 15 }{ 24 } +\frac { 36 }{ 24 } -\frac { 54 }{ 3 } +\frac { 45 }{ 2 } +9[/tex]
[tex]\\ \\ =\frac { 19 }{ 24 } -\frac { 54 }{ 3 } +\frac { 45 }{ 2 } +\frac { 18 }{ 2 } \\ \\ =\frac { 19 }{ 24 } -\frac { 54 }{ 3 } +\frac { 63 }{ 2 }[/tex]
[tex]\\ \\ =\frac { 343 }{ 24 } [/tex]
Answer: 343/24 units squared.
y = -2x² - 5x + 3
-2x² - 5x + 3 = 0
x = -(-5) +/- √(-5² - 4(-2)(3))
2(-2)
x = 5 +/- √(25 + 24)
-4
x = 5 +/- √39
-4
x = 5 +/- 6.244997998398398
-4
x = 5 + 6.244997998398398 x = 5 - 6.244997998398398
-4 -4
x = 11.624997998398398 x = -1.244997998398398
-4 -4
x = -2.8112494995996 x = 0.3112494995996
-----------------------------------------------------------------------------------------------
y = -2x² - 5x + 3 y = -2x² - 5x + 3
y = -2(-3)² - 5(-3) + 3 y = -2(0.3)² - 5(0.3) + 3
y = -2(9) + 15 + 3 y = -2(0.09) - 0.15 + 3
y = -18 + 15 + 3 y = -0.18 - 0.15 + 3
y = -3 + 3 y = -0.33 + 3
y = 0 y = 2.67
-----------------------------------------------------------------------------------------------
(x, y) = (-3, 0) (x, y) = (0.3, 2.67)
-2x² - 5x + 3 = 0
x = -(-5) +/- √(-5² - 4(-2)(3))
2(-2)
x = 5 +/- √(25 + 24)
-4
x = 5 +/- √39
-4
x = 5 +/- 6.244997998398398
-4
x = 5 + 6.244997998398398 x = 5 - 6.244997998398398
-4 -4
x = 11.624997998398398 x = -1.244997998398398
-4 -4
x = -2.8112494995996 x = 0.3112494995996
-----------------------------------------------------------------------------------------------
y = -2x² - 5x + 3 y = -2x² - 5x + 3
y = -2(-3)² - 5(-3) + 3 y = -2(0.3)² - 5(0.3) + 3
y = -2(9) + 15 + 3 y = -2(0.09) - 0.15 + 3
y = -18 + 15 + 3 y = -0.18 - 0.15 + 3
y = -3 + 3 y = -0.33 + 3
y = 0 y = 2.67
-----------------------------------------------------------------------------------------------
(x, y) = (-3, 0) (x, y) = (0.3, 2.67)
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.